2008
DOI: 10.1007/s00277-008-0462-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 20 deletions in myelodysplastic syndromes and Philadelphia-chromosome-negative myeloproliferative disorders: characterization by molecular cytogenetics of commonly deleted and retained regions

Abstract: Deletion of the long arm of chromosome 20 is a recurrent abnormality observed in myelodysplastic syndromes (MDS) and in Philadelphia-chromosome-negative myeloproliferative disorders (MPD). Our objective was to characterize the deletion size among 38 MDS and MPD patients using fluorescence in situ hybridization (FISH) with bacterial artificial chromosome (BAC) probes and to define commonly deleted and retained regions on chromosome 20. Patients were distributed in three groups according to the World Health Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 41 publications
2
36
0
1
Order By: Relevance
“…11 In MPD patients, del20q was found in the bone marrow from approximately 1% of patients with essential thrombocythemia (ET), up to 9% of polycythemia vera (PV) and up to 12% of primary myelofibrosis (PMF). 10,12 The del20q occurred preferentially together with the JAK2-V617F mutation in 28 of 29 MPD patients studied. 13 We previously analyzed 2 such patients with del20q and JAK2-V617F and found that the size of the del20q clone by far exceeded the size of the clone carrying JAK2-V617F, 14 suggesting that del20q preceded the acquisition of the JAK2-V617F mutation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…11 In MPD patients, del20q was found in the bone marrow from approximately 1% of patients with essential thrombocythemia (ET), up to 9% of polycythemia vera (PV) and up to 12% of primary myelofibrosis (PMF). 10,12 The del20q occurred preferentially together with the JAK2-V617F mutation in 28 of 29 MPD patients studied. 13 We previously analyzed 2 such patients with del20q and JAK2-V617F and found that the size of the del20q clone by far exceeded the size of the clone carrying JAK2-V617F, 14 suggesting that del20q preceded the acquisition of the JAK2-V617F mutation.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4] A common deleted region (CDR) of 2.7 megabases (Mb) was mapped for patients with MPD, and a 2.6-Mb CDR was defined for MDS/AML with an overlap of 1.7 Mb between the 2 CDRs. [5][6][7][8][9][10] However, to date, it was not possible to identify a gene mutation within the CDR that is functionally linked to the expansion of the del20q clone. 11 In MPD patients, del20q was found in the bone marrow from approximately 1% of patients with essential thrombocythemia (ET), up to 9% of polycythemia vera (PV) and up to 12% of primary myelofibrosis (PMF).…”
Section: Introductionmentioning
confidence: 99%
“…Misregulation of the dido gene is linked to increased incidence of genomic instability, myelodysplasia, and myeloproliferation, melanoma, and infertility (13,17,26,28). Elucidating the mechanisms that govern the complex activities could help clarify the role of Dido in promoting stem cell differentiation, cilia size, tumorigenesis and, as shown here, life expectancy, brain development, and neural behavior alterations.…”
Section: Discussionmentioning
confidence: 79%
“…However, there are also studies where no significant difference in median survival has been observed between patients with +8 as a single abnormality and patients with +8 associated with another cytogenetic abnormality. 7,10,13,[35][36][37][38] In our study, there were 10 patients with trisomy 8. In three of them, trisomy 8 was the only abnormality, in another three there was an additional abnormality and in four, a complex karyotype was detected.…”
Section: Discussionmentioning
confidence: 99%